Post COVID-19 vaccination headache: A clinical and epidemiological evaluation - Ceccardi, Giulia; Schiano di Cola, Francesca; Di Cesare, Marco; Liberini, Paolo; Magoni, Mauro; Perani, Cristiano; Gasparotti, Roberto; Rao, Renata; Padovani, Alessandro (Frontiers in Pain Research, 2022)
Introduction: aim of the present study was to assess the prevalence and clinical characteristics of post COVID-19 vaccination headache, in particular of secondary headaches. Methods: the present observational study was performed at the ASST Spedali Civili of Brescia. Admissions to the Emergency Department (ED) and subsequent hospitalizations regarding a new or worsening headache in the 16 days following the administration of the COVID-19 vaccine between January 2021 and January 2022 were recorded and compared to those of January 2019 – January 2020. Results: the ratio between ED admissions due to headache and total ED admissions was significantly higher in 2021 compared to 2019 (4.84% vs 4.27%; p<0.0001). Two-hundred and eighty-nine ED headache admissions (10.8% of all ED headache admissions) were time-correlated to the Covid-19 vaccination, of which 40 were hospitalized in order to exclude a symptomatic aetiology. At discharge, 32 patients had a diagnosis of benign headache not attributed to any cranial/extracranial disorder and eight patients of secondary headache, whose diagnoses were the following: Headache attributed to cranial and/or cervical vascular disorder (n=4), Headache attributed to non-vascular intracranial disorder (n=2), Headache or facial pain attributed to disorder of the cranium, neck, eyes, ears, nose, sinuses, teeth, mouth or other facial or cervical structure (n=1), Painful lesions of the cranial nerves (n=1). The headache most frequently reported by patients had migraine-like characteristics. Conclusions: Following the spread of Covid-19 vaccination, the number of ED admissions due to headache significantly increased. However, less than 14% of all the ED visits due to a headache time-correlated with the Covid-19 vaccination were actually hospitalised, with most patients documenting a benign headache, possibly related to the generic side effects of the vaccination. Only 8/40 hospitalized patients were diagnosed with a secondary headache. Benign headaches would actually fulfil diagnostic criteria for 8.1 Headache attributed to the use of or exposure to a substance (ICHD-3), although, at the time being, it does not include vaccines as possible substances. The headache migraine-like characteristics’ could suggest an activation of the trigeminovascular pathway by all the cytokines and other pro-inflammatory molecules released following the vaccination.